2020
DOI: 10.1093/nar/gkaa147
|View full text |Cite
|
Sign up to set email alerts
|

Locally acting transcription factors regulate p53-dependent cis-regulatory element activity

Abstract: The master tumor suppressor p53 controls transcription of a wide-ranging gene network involved in apoptosis, cell cycle arrest, DNA damage repair, and senescence. Recent studies revealed pervasive binding of p53 to cis-regulatory elements (CREs), which are non-coding segments of DNA that spatially and temporally control transcription through the combinatorial binding of local transcription factors. Although the role of p53 as a strong trans-activator of gene expression is well known, the co-regulatory factors … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…It is now appreciated that even though p53 seems to be able to regulate its target genes without cooperating with additional sequence-specific TFs ( 93 , 94 ), they can nonetheless contribute to p53-dependent transcriptional activation at some genomic binding sites ( 95 ). We suggest that the effect of nearby yeast cis-regulatory elements, and the TFs that bind them, may be an answer to the question of the significantly higher transactivation levels from RLminus relative to those from other p21-5′ variants studied here, when its binding characteristics (measured and predicted) are not different from those of the other variants.…”
Section: Discussionmentioning
confidence: 99%
“…It is now appreciated that even though p53 seems to be able to regulate its target genes without cooperating with additional sequence-specific TFs ( 93 , 94 ), they can nonetheless contribute to p53-dependent transcriptional activation at some genomic binding sites ( 95 ). We suggest that the effect of nearby yeast cis-regulatory elements, and the TFs that bind them, may be an answer to the question of the significantly higher transactivation levels from RLminus relative to those from other p21-5′ variants studied here, when its binding characteristics (measured and predicted) are not different from those of the other variants.…”
Section: Discussionmentioning
confidence: 99%
“…Another MPRA approach provided additional evidence for the role of other TFs in regulating p53 transcriptional activity. ( 149 ). Screening the transcriptional activity of thousands of variants of p53-bound regulatory elements revealed that other motifs flanking a p53RE contribute to p53-dependent activation.…”
Section: Functional Consequences Of P53 Binding In Varied Genomic Conmentioning
confidence: 99%
“…Screening the transcriptional activity of thousands of variants of p53-bound regulatory elements revealed that other motifs flanking a p53RE contribute to p53-dependent activation. One such example was binding of ATF3 and p53 to an enhancer element regulating expression of GDF15 ( 149 ). ATF3 and p53 have been previously shown to co-occupy many genomic locations, with ATF3 activity contributing to p53-dependent activation of numerous downstream targets ( 63 , 150 ).…”
Section: Functional Consequences Of P53 Binding In Varied Genomic Conmentioning
confidence: 99%
“…p53 is a common tumor suppressor that controls the transcription of extensive gene networks involved in apoptosis, cell cycle arrest, DNA damage repair, and aging[ 54 ]. Physiological p53 activity can prevent cancer and aging, while unrestricted and excessive p53 activity can promote aging [ 5 ].…”
Section: Molecular Mechanisms Of Cellular Senescence and Saspmentioning
confidence: 99%